Mixed odontogenic tumour with dentinoid and ghost cells. (23rd December 2015) - Kumar, Pavan; Jayam, Cheranjeevi; Patil, Shruthi; Zingade, Jyoti
Abstract : Ameloblastomas do not generally show evidence of induction, however, rare cases associated with odontome have been reported and are referred to as odontoameloblastomas. We report an unusual case of an ameloblastoma with features of an adenomatoid odontogenic tumour, showing evidence of induction of dentinoid by tumour cells—but without concomitant formation of enamel—and with features of ghost cells. The lesion occurred on the left side of the maxilla in a 31-year-old woman.